Social Entrepreneurship Model In Du'anyam MSMEs: A Case Study Of Women's Empowerment Through Traditional Woven Crafts - Febriyani, Yanik; Dewantoro, Tomy Wahyu; Sudarmiatin; Wijijayanti, Trisetia (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research aims to understand the social entrepreneurship model applied by Du'Anyam MSMEs in empowering women in remote areas through traditional woven production activities made from palm leaves. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with founders, field managers, and women artisans, as well as observations of production and marketing activities. The results of the study show that Du'Ayam's social entrepreneurship model emphasizes a balance between social, economic, and cultural values through the empowerment of local communities. Du'Anyam is able to integrate social missions in a sustainable business strategy that involves training, community-based production systems, and market penetration through products with modern designs and cultural stories. These findings reinforce that social entrepreneurship can be an effective strategy to realize inclusive development in the MSME sector.